Evaluate S S = 2 1 + 4 4 + 8 9 + 1 6 1 6 + 3 2 2 5 + ⋯
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Start with
∑ k = 0 ∞ x k = 1 − x 1 d x d ∑ k = 0 ∞ x k = d x d 1 − x 1 x ∑ k = 1 ∞ k x k − 1 = x ( 1 − x ) 2 1 d x d ∑ k = 1 ∞ k x k = d x d ( 1 − x ) 2 x x ∑ k = 1 ∞ k 2 x k − 1 = x ( 1 − x ) 3 1 + x ∑ k = 1 ∞ k 2 x k = ( 1 − x ) 3 x ( 1 + x )
Therefore,
∑ k = 1 ∞ 2 k k 2 = ∑ k = 1 ∞ k 2 ( 2 1 ) k = ( 1 − 2 1 ) 2 ( 2 1 ) ( 1 + 2 1 ) = 6
Woah, did you just think of this approach or is it some standard method?
Log in to reply
It's actually quite a standard procedure to solve convergent series like that!
S = k = 1 ∑ ∞ 2 k k 2 = k = 0 ∑ ∞ 2 k k 2 = k = 0 ∑ ∞ 2 k + 1 ( k + 1 ) 2 = 2 1 k = 0 ∑ ∞ 2 k k 2 + 2 k + 1 = 2 1 k = 0 ∑ ∞ 2 k k 2 + k = 0 ∑ ∞ 2 k k + 2 1 k = 0 ∑ ∞ 2 k 1 = 2 S + k = 0 ∑ ∞ 2 k + 1 k + 1 + 2 1 ( 1 − 2 1 1 ) = 2 S + 2 1 k = 0 ∑ ∞ 2 k k + 2 1 k = 0 ∑ ∞ 2 k 1 + 1 = 2 S + = S 1 2 S 1 + 1 + 1 = 2 S + 2 + 1 = 6 Again k = 0 ∑ ∞ 2 k k = k = 1 ∑ ∞ 2 k k = S 1 Since S 1 = 2 S 1 + 1 ⟹ S 1 = 2
Problem Loading...
Note Loading...
Set Loading...
S S − 2 1 S = k = 1 ∑ ∞ 2 k k 2 = 2 1 k = 1 ∑ ∞ 2 k − 1 ( k − 1 ) 2 + k = 1 ∑ ∞ 2 k ( 2 k − 1 ) = 2 1 S + k = 1 ∑ ∞ 2 k k + 2 1 k = 1 ∑ ∞ ( 2 k − 1 k − 1 ) = 2 1 S + 2 3 k = 1 ∑ ∞ 2 k k = 2 3 k = 1 ∑ ∞ 2 k k So we can write 3 1 S S = k = 1 ∑ ∞ 2 k k = 2 1 k = 1 ∑ ∞ 2 k − 1 k − 1 + k = 1 ∑ ∞ 2 k 1 = 2 1 ( 3 1 S ) + 1 = 6